2002
DOI: 10.1051/0004-6361:20020173
|View full text |Cite
|
Sign up to set email alerts
|

Nested-grid calculations of disk-planet interaction

Abstract: Abstract. We study the evolution of embedded protoplanets in a protostellar disk using very high resolution nestedgrid computations. This method allows us to perform global simulations of planets orbiting in disks and, at the same time, to resolve in detail the dynamics of the flow inside the Roche lobe of the planet. The primary interest of this work lies in the analysis of the gravitational torque balance acting on the planet. For this purpose we study planets of different masses, ranging from one Earth-mass… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
193
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(207 citation statements)
references
References 24 publications
(48 reference statements)
11
193
3
Order By: Relevance
“…Indeed, hydrodynamical simulations (Lubow et al 1999;D'Angelo et al 2002) have shown that, when the planet opens a gap in the disk, the accretion rate of gas is highly reduced. However, it has also been shown (see Kley & Dirksen 2006) that when the mass of the planet becomes of the order of 3−5 M (M is the mass of Jupiter ≈318 M ⊕ ), the disk-planet system can undergo a dynamic instability, leading to a substantial increase of the accretion rate of gas.…”
Section: Migration Ratementioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, hydrodynamical simulations (Lubow et al 1999;D'Angelo et al 2002) have shown that, when the planet opens a gap in the disk, the accretion rate of gas is highly reduced. However, it has also been shown (see Kley & Dirksen 2006) that when the mass of the planet becomes of the order of 3−5 M (M is the mass of Jupiter ≈318 M ⊕ ), the disk-planet system can undergo a dynamic instability, leading to a substantial increase of the accretion rate of gas.…”
Section: Migration Ratementioning
confidence: 99%
“…For example, the eccentric instability that justifies the assumption that the planetary gas accretion rate is the same as the disk accretion rate occurs only for planets larger than a certain mass (Kley & Dirksen 2006). At smaller masses, the accretion rate could be smaller (D'Angelo et al 2002). Also planet-planet interactions of several giant planets forming concurrently can have important consequences for the migration and accretion rate.…”
Section: Type II Migrationmentioning
confidence: 99%
“…This migration is generally described by two different regimes that depend on the mass of the protoplanet. The first is type I migration for low-mass planets, which are too small to form a gap in the disk, and the second is type II migration for planets that open a gap (D'Angelo et al 2002). A&A 567, A121 (2014) In our previous work (e.g., Mordasini et al 2009a;Alibert et al 2011), we used the results obtained for isothermal disks reported in Tanaka et al (2002) to calculate type I migration rates.…”
Section: Introductionmentioning
confidence: 99%
“…Grid-based hydrodynamical or smoothed particle hydrodynamical (SPH) simulations (D'Angelo et al 2002;Fouchet et al 2010), combined with follow-up radiative transfer simulations (Wolf et al 2002;Jang-Condell & Sasselov 2003;Wolf & D'Angelo 2005;Jang-Condell & Boss 2007;Jang-Condell 2009;Gonzalez et al 2010Gonzalez et al , 2012, have shown that largescale disk structures are visible through the continuum reemission and scattered light of the disk. The case of the observability of simulated line emission has been investigated A&A 549, A97 (2013) by Semenov et al (2008), Regály et al (2010), and Cleeves et al (2011).…”
Section: Introductionmentioning
confidence: 99%